APLIKASI PENDIDIKAN KECAKAPAN HIDUP (LIFE SKILLS) BERBASIS PENDIDIKAN AGAMA ISLAM DI SMP ISLAM AS-SUNNAH BAGIK NYAKA KEC. AIKMEL LOMBOK TIMUR NUSA TENGGARA BARAT TAHUN PELAJARAN 2024/2025 - Iskandar, Adi (UNISAN JURNAL, 2025)
The author employed a qualitative descriptive research method, emphasizing direct field observation and data analysis from existing sources. The results of this study indicate that Islamic education and life skills are inseparable components, as they are an integral whole in their relationship to life. This study also demonstrates that the concept of life skills can be used as a new direction for Islamic education, by integrating several aspects of life skills with Islamic education. From these results, it can be concluded that the application of life skills can provide students with abilities, capabilities, and skills in both information technology and religion. As a foundation for life, it is hoped that each student will possess personal, rational, social, academic, and vocational skills integrated within Islamic education. The results of this study are expected to serve as a constructive tool for improving the quality of Islamic education in the future, both theoretically and practically. Furthermore, the results of this study cannot be considered final; therefore, further research is expected to review these findings.